2013
DOI: 10.1038/cddis.2013.263
|View full text |Cite|
|
Sign up to set email alerts
|

HSP70 inhibition by 2-phenylethynesulfonamide induces lysosomal cathepsin D release and immunogenic cell death in primary effusion lymphoma

Abstract: Heat-shock protein (HSP) 70 is aberrantly expressed in different malignancies and has a cancer-specific cell-protective effect. As such, it has emerged as a promising target for anticancer therapy. In this study, the effect of the HSP70-specific inhibitor (PES), also Pifitrin-μ, on primary effusion lymphoma (PEL) cell viability was analyzed. PES treatment induced a dose- and time-dependent cytotoxic effect in BC3 and BCBL1 PEL cells by inducing lysosome membrane permeabilization, relocation of cathepsin D in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 44 publications
(65 reference statements)
3
70
0
Order By: Relevance
“…It has recently been described that a vicious circle of ROS-induced zinc release and zinc-driven mitochondrial ROS production is an important neuronal cell death mechanism 50 . On the other hand, it has been reported that the induction of a type of cell death other than apoptosis in cancer cells might increase the immunogenic potential of cell death 51,52 . Whether a change in the death process upon Zn (II) pre-exposure can affect the immune response to UV-damaged cells, which would impact the development of various pathologies, e.g., autoimmunity or cancers, must be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been described that a vicious circle of ROS-induced zinc release and zinc-driven mitochondrial ROS production is an important neuronal cell death mechanism 50 . On the other hand, it has been reported that the induction of a type of cell death other than apoptosis in cancer cells might increase the immunogenic potential of cell death 51,52 . Whether a change in the death process upon Zn (II) pre-exposure can affect the immune response to UV-damaged cells, which would impact the development of various pathologies, e.g., autoimmunity or cancers, must be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we investigated whether, besides ATG5, the increased CAPN activity would lead to the cleavage of other molecules such as BID, [56][57][58] whose truncated fragments have been reported to promote cell death. 59,60 Western blot analysis revealed the appearance of a BID-cleaved form in KSHV-infected and starved THP-1 cells that was not detectable in the presence of PD (Fig. 2E).…”
Section: Kshv-infected Cells Was Evaluated 30 H Post-infection By Immmentioning
confidence: 99%
“…There are also some evidences that several chemicals, such as benzylidene lactam, triptolide, emunine etc., inhibit hsp gene expressions by interacting with HSFs [108]. It is known that 2-phenylethynesulfonamide (PES, pifitrin-) is a specific inhibitor of stress-inducible HSP70, the usage of PES induces cell death in primary effusion lymphoma [127].…”
Section: Hsp Inhibition and Clinical Trialsmentioning
confidence: 99%